Barriers, Opportunities, and Challenges in Addressing Disparities in Diet‐Related Cardiovascular Disease in the United States. Issue 7 (9th April 2020) - Kris‐Etherton, Penny M.; Petersen, Kristina S.; Velarde, Gladys; Barnard, Neal D.; Miller, Michael; Ros, Emilio; O'Keefe, James H.; Williams, Kim; Horn, Linda Van; Na, Muzi; Shay, Christina; Douglass, Paul; et al.
Abstract: In the United States, cardiovascular disease (CVD) is the leading cause of death and disability. Suboptimal diet quality is responsible for a greater percentage of CVD‐related morbidity and mortality than any other modifiable risk factor. Further troubling are the stark racial/ethnic and socioeconomic disparities in diet quality. This represents a major public health concern that urgently requires a coordinated effort to better characterize the barriers to healthy dietary practices in population groups disproportionally affected by CVD and poor diet quality to inform multifaceted approaches at the government (policy), community environment, sociocultural, and individual levels. This paper reviews the barriers, opportunities, and challenges involved in shifting population behaviors, especially in underserved populations, toward healthy dietary practices. It is imperative that public health policies address the social determinants of nutrition more intensively than previously in order to significantly decrease CVD on a population‐wide basis.